P153 The impact of seton use on clinical and patient-reported outcomes in Crohn's disease perianal fistulas: findings from a systematic literature review. (21st January 2022) - White, I; Karki, C; Geransar, P; Worsfold, A; Leisle, L; Junker, S; Fleshner, P
Abstract: Background: Complex perianal fistulas are a common complication of Crohn's disease, and are treated with both surgical and medical intervention. Irrespective of treatment strategy, seton placement is used to facilitate fistula drainage and prevent recurrent abscess formation. The aim of this systematic literature review was to summarize available evidence on clinical outcomes associated with seton use for symptomatic relief and treatment of complex Crohn's perianal fistula (complex CPF). Methods: Electronic databases (MEDLINE, Embase, EBM Reviews and Econlit) were searched for articles (1980–present) reporting data on the use of seton in patients with complex CPF. Seton use as a preparatory procedure for surgery was excluded. Articles were screened for relevance using pre-defined PICOS-T criteria and data on outcomes of interest including clinical remission, fistula recurrence, adverse events, and patient-reported outcomes (PROs) were extracted. Data were summarized qualitatively and analysed using descriptive statistics. Results: Overall, 56 articles underwent data extraction (43 full texts, 13 congress abstracts; 50 observational studies, 6 clinical trials). Duration of seton use was reported in 23 studies (range: 4–277 weeks). Clinical response and/or remission following seton use or seton use + biologics were defined by 35 articles. Definitions were variable, with most relating to fistula closure, symptom improvement or cessation of fistula drainage. Remission rates in patients treated with seton only and seton + infliximab were 13–75% (9 articles) and 23–100% (14 articles), respectively (Figure). Definitions of recurrence (e.g. fistula discharge or reopening) were reported in 16 observational studies and varied. Most articles defined clinical outcomes (e.g. prior removal of seton, closure or healing of the fistula tract, or response) before recurrence was measured. Overall, recurrence rates in patients treated with seton only and seton + infliximab were 4–68% (9 articles) and 0–50% (12 articles), respectively (Figure). The rate of recurring abscesses (3 articles) or local sepsis (2 articles) and the frequency of new abscess (7 articles) or fistula development (3 articles) was 7–43%, 31–61%, 10–47% and 9–26%, respectively. Rates of adverse events or complications after seton use (14 articles) ranged from 0–77%. PROs measuring functional outcomes, faecal incontinence and quality of life were reported by 6 articles. Conclusion: Owing to a lack of standardized definitions for clinical outcomes following seton use in complex CPF, comparison of study results was not possible. Standard clinical outcome definitions are needed to permit data comparability, and are vital to guide treatment plans to improve outcomes for patients with complex CPF.